Functional characterization of kurtz, a Drosophila non-visual arrestin, reveals conservation of GPCR desensitization mechanisms. - Johnson, E.C.; Tift, F.W.; McCauley, A.; Liu, L.; Roman, G. (Insect Biochemistry and Molecular Biology, 2008)
The arrestins are a family of molecules that terminate signaling from many different G protein-coupled receptors, by inhibiting the association between receptor and downstream effectors. We recently employed a human betaarrestin2-GFP fusion protein to explore the dynamics of different neuropeptide receptors in Drosophila and have previously used a betaarrestin translocation assay to identify ligands at orphan receptors. Here, we report that the Drosophila arrestin encoded by kurtz functions in a similar fashion and can be employed to investigate GPCR-arrestin associations. Specifically, a GFP-krz fusion protein, upon co-expression with various Drosophila peptide receptors, an amine receptor, and a mammalian peptide receptor translocates to the plasma membrane in specific response to ligand application. This molecular phenotype is exhibited in a mammalian cell line as well as in a Drosophila cell line. Notably, the details of receptor-arrestin associations in terms of endocytotic patterns are functionally conserved between the mammalian arrestins and kurtz. Furthermore, we report that kurtz mutants exhibit hypersensitivity to osmotic stress, implicating GPCR desensitization as an important feature of the endocrine events that shape this stress response.